INTER-RELAÇÕES ENTRE GESTÃO ESCOLAR, FORMAÇÃO DE PROFESSORES E METODOLOGIAS ATIVAS: PERSPECTIVAS EDUCATIVAS PARA O ENSINO INOVADOR NA CONTEMPORANEIDADE - Santos, Marta da Cunha (2021)
In this study, we sought to analyze the interrelationships between school management, teacher training and active methodologies in order to contribute to the qualification of school teaching practice, with a view to innovative teaching compatible with contemporaneity. The dissertation is organized into five (5) chapters, in addition to the introduction and final considerations. In the first chapter, the methodological design of the study is described, which includes a qualitative approach, based on the bibliographic research method, through which we sought to use the theoretical assumptions of different authors, as a way to support the intended reflection. The second chapter deals with the theoretical and legal assumptions, which guide school management, and also aims to highlight the important role played by the manager in educational institutions. The third chapter discusses teacher training and the qualification of school education. In this chapter, it is proposed to identify the conceptions and trends in teacher education today and teacher education as an area of knowledge and its contribution to the qualification of school education. The fourth chapter deals with Active Methodologies and their contributions to innovative teaching, as well as to the qualification of school education and construction of student learning. An integrative synthesis of the study is presented in the fifth chapter, in which the triangulation of knowledge is carried out, based on the model proposed by Nóvoa (1999). The interrelationships between School Management, Teacher Education and Active Methodologies are presented, whose center of this triangulation is occupied by the student. As conclusions, management is pointed out as a pillar in the organization of systematic actions within the school, enabling the qualification of educational services, in the permanent search for teaching excellence; teacher training, as essential to the qualification of teaching practice and active methodologies as fundamental in the proposition of innovative teaching compatible with society in times of change and the expectations of students in the light of contemporaneity.